Assessing Differences in Anthropometric and Fitness Characteristics Between Police Academy Cadets and Incumbent Officers. Issue 9 (September 2018) - Orr, Robin M.; Dawes, J. Jay; Pope, Rodney; Terry, Joseph
Abstract : Abstract: Orr, RM, Dawes, JJ, Pope, R, and Terry, J. Assessing differences in anthropometric and fitness characteristics between police academy cadets and incumbent officers. J Strength Cond Res 32(9): 2641–2650, 2018—The physical fitness of police officers must be developed in new cadets and sustained in incumbent officers. The aims of this study were to profile and compare the anthropometric and fitness characteristics of police academy cadets and incumbent officers of varying ages from a single police force. Retrospective data for 84 police academy cadets (♂ = 66, mean age = 27.96 ± 5.73 years; ♀ = 18, mean age = 30.50 ± 5.76 years) and 80 incumbent police officers (♂ = 73, mean age = 39.43 ± 8.28 years; ♀ = 7, mean age = 37.86 ± 3.67 years) were compiled. Data included participant age, anthropometric (body mass, lean mass, and fat mass), and fitness measurements (1-minute push-up, 1-minute sit-up, 1 repetition maximum bench press, vertical jump, 300-m, and 1.5-mile run). Male cadets exhibited significantly lower fat mass than male officers (12.4 vs. 15.1 kg, p = 0.003). These differences were fully explained by the age differences between these groups ( p = 0.046). Male cadets were more aerobically fit with greater muscular endurance than male officers ( p < 0.001 for all measures). This difference was not explained by age differences ( p > 0.80 for all measures). Male cadets also exhibited higher anaerobic fitness than male officers ( p < 0.001). Age differences only partially explained this difference ( p = 0.01). Female cadets exhibited greater upper-body strength and muscular endurance than female officers ( p < 0.004 for all measures), independent of age. Being a police officer, rather than age progression, may largely account for observed lower levels of fitness in incumbent officers when compared with cadets. Formalized physical training programs for incumbent police officers are needed if their fitness is to be maintained and risk of cardiovascular disease minimized.